A STUDY ON VARIATION IN BIOCHEMICAL ASPECTS OF DIFFERENT TREE SPECIES WITH TOLERANCE AND PERFORMANCE INDEX - BORA, MEHA; JOSHI, NAMITA (The Bioscan, 2013)
The present study was undertaken to evaluate the variation between biochemical characteristics and air pollution tolerance index (APTI) of 6 different plant species. The results of the present study indicate that APTI was significantly correlated with total chlorophyll, ascorbic acid, leaf pH for all species and are the most significant and determining factors on which the tolerance depends. The order of tolerance index of plant species is as follows Saraca indica (13.71), Azadirachta indica (12.98), Shorea robusta (12.64), Eucalyptus sp. (12.61), Ficus religiosa (12.61) and Tectona grandis (13.33). According to anticipated performance index (API) all species were tolerant i.e. Azadirachta indica, Ficus religiosa, Saraca indica, Tectona grandis (75%), Shorea robusta and Tectona grandis (68%). The present study suggests that evaluation of plant tolerance and performance index might be very useful in the selection of appropriate species which can be expected to perform well for the development of green environment.